Analisis Penerapan Prinsip Etika Bisnis Islam dalam Praktik Bisnis Isi Ulang Parfum - Cahyono, Andi; Mahdi, Imam; Iqbal, Moch. (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2024)
This research aims to analyze whether the Perfume Refill Business in Bengkulu has implemented the principles of Islamic business ethics in perfume refill sales transactions and how the principles of Islamic business ethics are applied in perfume refill transactions in Bengkulu. This research uses descriptive qualitative methods with data collection techniques in the form of interviews and documentation. The primary data in this research are the owners of perfume refills in Bengkulu, such as Edelwiss Parfum, Sempono, Althea Parfum, Pafum Ce-Le, in perfume, Al-Fazza perfume and consumers who buy perfume refills. The research results state that Perfume Refill in Bengkulu has fully implemented the principles of Islamic business ethics in its buying and selling, with the principle of monotheism, the principle of balance, the principle of free will, the principle of responsibility and the principle of ihsan.